Bulk‐Like Electrical Properties Induced by Contact‐Limited Charge Transport in Organic Diodes: Revised Space Charge Limited Current. (22nd February 2018) - Xu, Guangwei; Gao, Nan; Lu, Congyan; Wang, Wei; Ji, Zhuoyu; Bi, Chong; Han, Zhiheng; Lu, Nianduan; Yang, Guanhua; Li, Yuan; Liu, Qi; Li, Ling; et al.
Abstract: Charge transport governs the operation and performance of organic diodes. Illuminating the charge‐transfer/transport processes across the interfaces and the bulk organic semiconductors is at the focus of intensive investigations. Traditionally, the charge transport properties of organic diodes are usually characterized by probing the current–voltage ( I – V ) curves of the devices. However, to unveil the landscape of the underlying potential/charge distribution, which essentially determines the I – V characteristics, still represents a major challenge. Here, the electrical potential distribution in planar organic diodes is investigated by using the scanning Kelvin probe force microscopy technique, a method that can clearly separate the contact and bulk regimes of charge transport. Interestingly, by applying to devices based on novel, high mobility organic materials, the space‐charge‐limited‐current‐like I – V curves, which are previously believed to be a result of the bulk transport, are surprisingly but unambiguously demonstrated to be caused by contact‐limited conduction. A model accounting is developed for the transport properties of both the two metal/organic interfaces and the bulk. The results indicate that pure interface‐dominated transport can indeed give rise to I – V curves similar to those caused by bulk transport. These findings provide a new insight into the charge injection and transport processes in organic diodes. Abstract : The charge transport properties of organic diodes are detected as contact‐limited current using the scanning Kelvin probe force microscopy technique, a direct method that can clearly separate the contact and bulk regimes of charge transport. In addition, a model accounting for the transport properties of both the two metal/organic interfaces and the bulk is developed.